Improving Students Creativity In Writing Narrative Text Using Marathon Technique : A Study Of Tenth Grade Student Of SMAN 1 Lingsar - Riza Jayanti; Heri Hidayatullah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Creativity is an important component of global competition in the 21st century. Increasing students’ creativity is a great challenge for every educational institution. Education should be able to stimulate student creativity. The learning environment should be able to help students to develop their creativity so that students are able to optimize their ability. Students must be prepared to survive in real life. Therefore, students need to improve communication, action and creativity. From the pre-observation result of English teaching and learning process at tenth grade of SMAN 1 Lingsar, the researcher found that at least three problems faced by the students in their writing creativity. First, students lack initiative to make writing work during on after class. Second, they appeared reluctant when asked to write during class. Third, they showed disengagement when writing activities occurred in the classroom. This research has an aim to improve the students’ creativity in writing narrative text by using marathon technique, therefore, this research can be categorized into classroom action research (CAR).Based on research findings, Marathon Technique is able to improve students’ creativity in writing narrative text, students have improved their creativity in writing narrative text as it is proven by the score that the students achieved in their post-test compared to those in pretest. In pre-test, there were only 6 students got passing criteria of creativity, it was different with the post-test 1, which the students passing criteria of creativity are 13 students that accounted for 61% of success rate. In post-test 2 the students who passed criteria of creativity were 20 students (95%).The students and teachers’ perceptions towards the use of Marathon Technique were very good as indicated by their response from interview. The students and teachers’ perceptions were good in teaching writing using Marathon Technique as media especially in writing narrative text at tenth grade student of SMAN 1 Lingsar